An E-learning System in Malaysia based on Green Computing and Energy Level - Arif Ullah; Nazri Mohd Nawi; Asim Shahzad; Sundas Naqeeb Khan; Muhammad Aamir (Society of Visual Informatics, 2017)
The increasing of energy cost and also environmental concern on green computing gaining more and more attention. Power and energy are a primary concern in the design and implementing green computing. Green is of the main step to make the computing world friendly with the environment.Â In this paper, an analysis on the comparison of green computer with other computing in E-learning environment had been done. The results show that green computing is friendly and less energy consuming. Therefore, this paper provide some suggestions in overcoming one of main challenging problems in environment problems which need to convert normally computing into green computing. In this paper also, we try to find out some specific area which consumes energy as compared to green computing in E â€“learning centre in Malaysia. The simulation results show that more than 30% of energy reduction by using green computing.